Beyond the Limits: Memories, Silences, and Affections in "Secrets of Struggle" (2007) - Rivero, Elizabeth G. (Tropelías: Review of Literary Theory and Comparative Literature, 2024)
The documentary Secretos de lucha, produced by French film company S.M.A.C, is director´s Maiana Bidegain (1977) debut film. Born in Bayona, France, Bidegain is the daughter of exiles of the Uruguayan civilian-military dictatorship (1973-1985). In this film, the filmmaker attempts to unveil her family history, as censored, fragmented, and plagued by silences as that of her national community. Drawing on an interdisciplinary framework thar brings together Memory Studies, Film Studies, and the Theory of Affects, I propose that Bidegain´s documentary traverses and trespasses different discursive, conceptual, and aesthetic limits to examine the possibilities and challenges of reconstructing the memory of the recent past in her capacity as daughter of direct victims of the Uruguayan dictatorship. For that purpose, Secretos de lucha explores alternative modes of acquiring knowledge through the affective potential of film, and promotes the ethical and political engagement of spectators with the events of the dictatorial past and its legacy.